2011
DOI: 10.1017/s1744552311000048
|View full text |Cite
|
Sign up to set email alerts
|

Integrating human rights in emerging regulation of Corporate Social Responsibility: the EU case

Abstract: This article analyses the EU Commission's policy-based approach to regulating Corporate Social Responsibility (CSR) and the role of international human rights law as a normative source for the regulatory output in two initiatives launched in 2002 and 2006. The article argues as a starting point that the understanding of CSR as ‘beyond law’ tends to shroud the contributions that international human rights law and legal theory based regulatory technique lend to CSR normativity and regulation, not only outside th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 47 publications
0
35
1
Order By: Relevance
“…A vast literature has focused on the nature, role and the dynamics of corporate social responsibility. More recently, an emerging body of literature is examining the need for regulating CSR and the role of law (Abah, 2016;Amao, 2013;Buhmann, 2006;Buhmann, 2011;Dentchev, Haezendonck, & van Balen, 2017;Idemudia & Kwakyewah, 2018;Malesky & Taussig, 2017;Malesky & Taussig, 2019;Nieto, 2005;Okoye, 2016;Osuji, 2011;Osuji, 2015;Situ, Tilt, & Seet, 2018;Thirarungrueang, 2013). However, imposition of regulation on corporates for CSR faces several challenges in the absence of consensus on the nature of obligations that businesses have under current CSR models.…”
mentioning
confidence: 99%
“…A vast literature has focused on the nature, role and the dynamics of corporate social responsibility. More recently, an emerging body of literature is examining the need for regulating CSR and the role of law (Abah, 2016;Amao, 2013;Buhmann, 2006;Buhmann, 2011;Dentchev, Haezendonck, & van Balen, 2017;Idemudia & Kwakyewah, 2018;Malesky & Taussig, 2017;Malesky & Taussig, 2019;Nieto, 2005;Okoye, 2016;Osuji, 2011;Osuji, 2015;Situ, Tilt, & Seet, 2018;Thirarungrueang, 2013). However, imposition of regulation on corporates for CSR faces several challenges in the absence of consensus on the nature of obligations that businesses have under current CSR models.…”
mentioning
confidence: 99%
“…1223 Buhmann notes that this understanding of CSR 'has led to an idea that CSR and law are distinct'. 1224 In fact, this thesis has shown that there are direct overlaps between CSR and provisions in company law and causes of action in tort law with CSR whereas contract law and consumer law rather provide means for the incorporation and enforcement of CSR commitments, e.g. in supply chain contracts.…”
Section: Csr Is At Least In Part Lawmentioning
confidence: 99%
“…The IJLC very much reflects the breadth and depth of Michael's formidable intellect, his constant searching for new ways of understanding law and legal process, and his talent for making important connections and foregrounding context. A review of the most downloaded papers of the Journal over the past ten years reads like a record of Michael's projects and interests (and which have clearly found a grateful audience in academics developing their own work in these areas): mental health and incapacity, 12 analytical jurisprudence, 13 justice, 14 human rights, 15 courtroom evidence, 16 racism, 17 homophobia and bullying, 18 corporate responsibility 19 and marriage in its various forms. 20 Even this very partial review of the rich diversity of papers published in the IJLC over the past ten years gives us a clear picture of Michael's conception of 'law in context'.…”
Section: A Tributementioning
confidence: 99%